Natural killer cell in systemic lupus erythematosus. Defects in effector lytic activity and response to interferon and interferon inducers. - W L Sibbitt Jr; P M Mathews; A D Bankhurst (The Journal of Clinical Investigation, 1983)
Spontaneous cytotoxicity mediated by natural killer (NK) cells is impaired in several human diseases including systemic lupus erythematosus (SLE). The precise mechanism(s) by which NK activity is suppressed in patients with SLE is generally unknown. The present study was designed to focus on cellular defects per se in NK cells from patients with SLE. It was observed that the usual enhancing effect of interferon (IF) and IF inducers was markedly impaired in SLE patients. Of 24 SLE patients studied, 17 had significantly decreased NK activity relative to controls. NK activity had a significant negative correlation with clinical activity score (r = -0.56, P less than 0.005) but was not correlated with corticosteroid dose, antinuclear antibody titers, total hemolytic complement (CH50), or sedimentation rate. Furthermore, significant depressions in NK activity correlated with variations in disease activity in six patients followed serially. Depressed NK function could not be reversed by prolonged in vitro incubation at 37 degrees C or with protease treatment. Furthermore, depressed NK activity was not altered by removal of glass adherent cells nor was a suppression of NK activity in normal controls seen by the addition of SLE peripheral mononuclear cells. No reversal of depressed activity to normal levels was seen by the addition of indomethacin nor did the supernatants from SLE cell cultures cause a suppression of normal NK function. NK activity in SLE patients did not respond normally to IF inducers (poly-I:C and concanavalin A) even if the SLE patients had normal NK function. The response of SLE cells to exogenous IF was also impaired. The number of effector-target conjugates was quantitated with several target cells (K562, Yac-1, Fravel) in SLE patients and controls. A significant correlation between the proportion of glass nonadherent mononuclear cells that formed effector-target conjugates with these various targets and the magnitude of NK lysis was observed. However, SLE and normal subjects had equal numbers of effector-target conjugates independent of NK function. Release of a soluble cytotoxic factor was induced with concanavalin A, and was markedly impaired in SLE patients relative to normal controls. Thus, impaired NK cell function in SLE does not appear to be related to cell-mediated suppressive mechanisms or to the deletion of effector cells; rather, the decreased NK activity may be related to an impaired release of a soluble cytotoxic factor.